Analisis Kesiapan Industri Konveksi Kain Perca dalam Menghadapi Masyarakat Ekonomi Asean 2015 (Studi Kasus: Kelurahan Tipes Kecamatan Serengan, Surakarta) - Ramadhan, Rahmat; , Muchlison Anis ST.,MT; , Mila Faila Sufa ST.,MT (2016)
Fashion industry has been growing rapidly in Indonesia proved we have encountered many businesses such as garment, tailor, dressmaker, and convection. But the impact of these activities one of them a rag or cloth material waste. Solo Tipes precisely in the Village is the center of the utilization of patchwork to be products such as children's clothes, nightgowns, pants and so it encourages local governments to assist the business community through a community that has been formed. On the other hand in December 2015 already in berlakukannya ASEAN Economic Community (AEC) which indirectly free flow of goods to enter the territory of Indonesia. The purpose of this study to determine the readiness, the problem in convection patchwork face of MEA 2015. This study uses Multiple Linear Regression Analysis to determine the relationship between the independent variable on the dependent variable. Some indicators are elements pertinent to the preparation of AEC 2015 such as the flow of goods Free, Skilled Manpower, Capital, Marketing Strategy, and Role of Government that will these indicators will be tested with proper test instrument, classic assumption test and multiple linear regression. The results of the Multiple Linear Regression analysis found that variables of labor, capital, and the government's strategy has a positive value on the readiness of MEA (free goods flow) but variable role of government has a negative value to the readiness of the MEA. At t test variable capital this case demonstrated a significant effect t value 2,052> t table 2.048 with a significance value (Sig.) 0.048 <0.05. Variable skilled labor not significant because t value of 0.722 <t table 2.048 and significant values (Sig.) 0.477> 0.05. Variable Marketing Strategy not significant because t value 1.196 <t table 2.048 with significant values (Sig.) 0,243> 0.05. Variable role of government not significant because the value of -0.723 t <t table 2.048 with significant values (Sig.) 0.477> 0.05.